Carriage of Neisseria Species in Communities with Different Rates of Meningococcal Disease - Nicole Le Saux; Fraser Ashton; Maksudar Rahman; Alan Ryan; Edward Ellis; Susan Tamblyn; Joan Morris; Al Borczyk; Caroll Mallory; Donald Mikel; Stephen Thompson; Lyall Black; et al. (Canadian Journal of Infectious Diseases)
A single clone, Neisseria meningitidis serogroup C (C:2a:P1.2), was isolated from seven patients during a cluster of cases of meningococcal disease in Ontario in 1989. To determine whether the clone was present in asymptomatic individuals in the same population, pharyngeal swabs were taken from 7% (644 of 9125) of residents who were vaccinated during the outbreak. Rates of isolation of Neisseria species were also compared to those in two other geographical areas which did not have an elevated incidence of meningococcal disease. The rate of carriage of N meningitidis in the asymptomatic individuals sampled was between 1.9% and 5.4%. The clone isolated from patients was not present among the carrier strains as determined by sero- and subtyping and electrophoretic analysis of metabolic enzymes. Age greater than six years was the only factor associated with colonization with N meningitidis.